Climate change governance in forestry and related sectors: Respondents’ attitudes in selected forest regions and national parks in Serbia - Stanišić Mirjana; Nedeljković Jelena; Nonić Dragan (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2022)
Effectively combating climate change involves recognition of its negative environmental, economic and social impacts. Climate change governance requires the participation of stakeholders from different sectors, and the alignment of their interest and influence in the decision-making process. This paper aims to determine the attitudes of respondents towards the existence of climate change and assess their negative impact on forestry, forest ecosystems and protected areas. In addition, the goal is to identify differences in the assessment of interest and influence between stakeholders in climate change governance in selected forest regions and national parks in Serbia. Primary data were collected through interviews (103 in total), in the period from March 2017 to July 2019, with representatives of organizations from the public and civil sector, who deal with issues of forestry, nature conservation and climate change. Respondents believe that climate changes have a negative environmental, social and economic impact on forestry, forest ecosystems and protected areas. It was found that there are differences in interest and influence in climate change governance between stakeholders, regardless of sectoral affiliation. In addition, stakeholder influence assessments were found to be lower than interest in climate change governance. Opportunities for enhancing stakeholder interest and influence in climate change governance have been proposed.